2005
DOI: 10.1037/0735-7028.36.2.180
|View full text |Cite
|
Sign up to set email alerts
|

The Scope and Impact of Perinatal Loss: Current Status and Future Directions.

Abstract: The loss of an expected child can be devastating and traumatizing for parents, placing them at risk for postloss mental health complications, such as complicated or traumatic grief. The authors review the psychological and social impacts of perinatal loss and describe the standard care provided in the hospital. The authors review studies that examine the efficacy of standard care and highlight the need for empirical evidence confirming the efficacy of these current interventions. The authors provide recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 28 publications
2
92
0
5
Order By: Relevance
“…In the last few decades, providers have recognized that the death of a fetus or young infant can cause prolonged or complicated bereavement for many parents. [1][2][3][4] Health care providers are on the front lines, offering bereaved families comfort and support, helping parents say goodbye to their deceased infant and educating about the grieving process. Interviews with parents have demonstrated that health care providers can make families feel either supported or helpless after their infant or child dies.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, providers have recognized that the death of a fetus or young infant can cause prolonged or complicated bereavement for many parents. [1][2][3][4] Health care providers are on the front lines, offering bereaved families comfort and support, helping parents say goodbye to their deceased infant and educating about the grieving process. Interviews with parents have demonstrated that health care providers can make families feel either supported or helpless after their infant or child dies.…”
Section: Introductionmentioning
confidence: 99%
“…8 Women may experience psychological problems such as grief, depression, and anxiety. 9 Some health personnel may not be aware of the extent to which these problems are manifested. 10 Identifying psychological problems and providing counselling to such women is much needed to address their fear of problems in future pregnancies and family life.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that the perinatal loss literature indicates that women who experience perinatal loss often report selfblame (Bennett et al, 2005;De Frain et al, 1990;McGreal, Evans, & Burrows, 1998;Woods & Woods, 1997). Self-blame is additionally reported in studies of medical patients, such as cancer and heart disease patients.…”
Section: A Supplemental Findingmentioning
confidence: 99%
“…Unfortunately, researchers (Bennett et al, 2005) have reported that society often views perinatal loss, contrary to other child losses, as insignificant which is likely to leave mothers feeling alone and invalidated in their grief. Rajan (1994) pointed out that women may discover that pregnancy losses are not always viewed by others as significant emotional experiences.…”
mentioning
confidence: 99%
See 1 more Smart Citation